KAJIAN PROSES PENYULINGAN UAP MINYAK JINTAN PUTIH - Tri Yogo Wibowo, ), Suryatmi R.D, Meika Syahbanna Rusli dan Imelda H. S. (Department of Agroindustrial Technology, Bogor Agricultural University, 2007)
ABSTRACTCumin seed (Cuminum Cyminum Linn.) is the one of essential oil resources which is being developed for its economic value and one of the most used resources in pharmaceutical industries and flavourings. Cumin oil was able to cure some digestion problems, an antioxidants, highly anesstesive and fixative. Major component of cumin oil is cuminaldehyde,which reach 35-62%.This research aims to study cumin oil distillation character with steam distillation method and to know effect of steam pressure and bulk density to yield and physicochemical properties of cumin oil produced. Stages on this research were moisture content, essential oil content and ash content analyses, diatillation time determination, cumin oil distillation on different steam pressure and bulk density, and then analyzed. Cumin oil analyses consist of its yield, specific gravity, refractive index, optic rotation, acid number, ester value and solubility in alcohol 80%.This research used factorial complete randomized design with two factors. First factor was bulk density, which consists of two levels (0,1 and 0,2 kg/L). Second factor was steam pressure, which consists of three levels (0; 0,5; and 1 bar gauge). Analyzed data showed that its moisture content, essential oil and ash content respectively was 7,83%, 3,34% and 5,36%. Distillation time was in five hours, when 95% oil has been distillated.Steam pressure significantly affect the yield, specific gravity and ester value, which bulk density significantly affects its acid number and ester value. Interaction between these two factors significantly affects its yield and ester value. Cumin oil in this research was bright yellow to brown in color, with strong and spesific odor. Its yield was 1,23-2,65 % (bb), specific gravity was 0,9630-0,9862, refractive index was 1,497-1,504, optic rotation was +2,4°-+3,6°, and average comparison of its solubility in alcohol 80% was 1:2.The volatile oil composition of cumin oil was investigated by gas chromatography. The highest cuminaldehyde content as the major component of cumin oil was obtained from no steam pressure gauge.Keyword : minyak jintan, cuminaldehid, penyulingan uap